2015
DOI: 10.1097/ta.0000000000000600
|View full text |Cite
|
Sign up to set email alerts
|

A controlled resuscitation strategy is feasible and safe in hypotensive trauma patients

Abstract: BACKGROUND Optimal resuscitation of hypotensive trauma patients has not been defined. This trial was performed to assess the feasibility and safety of controlled resuscitation (CR) versus standard resuscitation (SR) in hypotensive trauma patients. METHODS Patients were enrolled and randomized in the out-of-hospital setting. 19 EMS systems in the Resuscitation Outcome Consortium participated. Eligible patients had an out-of-hospital systolic blood pressure (SBP) ≤ 90 mmHg. CR patients received 250 cc of fluid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
124
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(127 citation statements)
references
References 38 publications
1
124
0
2
Order By: Relevance
“…22 Several clinical studies have shown either improved outcome 23 or no difference 24,25 in civilian patients randomized to hypotensive versus normotensive resuscitation. However, these studies were performed in urban environments where prehospital transport times are relatively short.…”
Section: Remote Damage Control Resuscitation (Rdcr)mentioning
confidence: 99%
“…22 Several clinical studies have shown either improved outcome 23 or no difference 24,25 in civilian patients randomized to hypotensive versus normotensive resuscitation. However, these studies were performed in urban environments where prehospital transport times are relatively short.…”
Section: Remote Damage Control Resuscitation (Rdcr)mentioning
confidence: 99%
“…52 A multicenter pilot trial by ROC randomized 192 prehospital hypotensive trauma patients to high (110 mmHg) and low (70 mmHg) SBP goals and reported improved 24-hour survival in the low SBP group after blunt trauma (97% versus 82%), but no difference after penetrating trauma (81% versus 81%). 53 Significantly, all of the randomized trials cited above excluded patients with significant head injury.…”
Section: Pharmacologic Treatment Optionsmentioning
confidence: 99%
“…Schreiber et al performed a randomized pilot trial to compare the effect of controlled resuscitation (CR) with standard resuscitation (SR) in the pre-hospital scene [38] ( Table 2). The mean (standard deviation) crystalloid volume administered during the pre-hospital period was 1.0 (1.5) L in the CR group and 2.0 (1.4) L in the SR group.…”
Section: Clinical Trials Examining Restricted/controlled Resuscitationmentioning
confidence: 99%